Stability of Daptomycin in Dextrose and Icodextrin-Based Peritoneal Dialysis Solutions - Kai Ming Chow; Siu Kwan Wo; Simon Wai Yin So; Phyllis Mei Shan Cheng; Keary Rui Zhou; Wai Li Lim; Joan Zhong Zuo; Philip Kam Tao Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusions: Current stability results support and guide the use of intraperitoneal daptomycin in different dialysis solutions. Patients with peritonitis requiring icodextrin exchange and assisted preparation of daptomycin can benefit from nurses who provide daily home visit based on our stability results.